1972
DOI: 10.1039/c39720000113
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the natural products blumenols A, B, and C

Abstract: Blumenols A, B, and C, new compounds from Podocarpus blumei, are shown to have structures (I), (2), and (3), respectively, with the opposite stereochemistry to that of abscisic acid (4) at the ring chiral centre. CHROMATOGRAPHY of the extract of the leaves of Podocarpus blumei Endl., afforded three new compounds, named blumenol A, B, and C, which showed strong U.V. absorption at 236 nm. Blumenol A, C13H2003 (microanalysis and M+ ion at m/e 224), m.p. 114-116', formed a monoacetate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1974
1974
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…The spectroscopic data of the disaccharide moiety and those of the aglycone, compared with literature data (Galbraith and Horn, 1972;Miyase et al, 1988), unambiguously identified blumenin as a new natural blumenol C glycoside. With regard to the elucidation of the structure and its occurrence, there is no systematic distribution of blumenol C and its conjugates in plants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The spectroscopic data of the disaccharide moiety and those of the aglycone, compared with literature data (Galbraith and Horn, 1972;Miyase et al, 1988), unambiguously identified blumenin as a new natural blumenol C glycoside. With regard to the elucidation of the structure and its occurrence, there is no systematic distribution of blumenol C and its conjugates in plants.…”
Section: Discussionmentioning
confidence: 97%
“…With regard to the elucidation of the structure and its occurrence, there is no systematic distribution of blumenol C and its conjugates in plants. The aglycone of blumenin, blumenol C, was found for the first time, together with its possible deriv a t' ives blumenol A and B, in leaves of Podocarpus blumei (Podocarpaceae) (Galbraith and Horn, 1972). A blumenin-related glycoside, blumenol C glucoside, has been isolated from leaves of Nicotiana rustica (Solanaceae) (Kodama et al, 1984) and Isatis tinctoria (Brassicaceae) (Hartleb and Seifert, 1994) and the aerial parts of Epimedium grandiflorum (Berberidaceae) (Miyase et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…,32) The asymmetric center in the side chain of the isolated compound displayed an optical rotation and the absolute configuration at C(9) was shown to be R. This fact indicates that in the degradation pathway of carotenoids to (45) OH o (39) o (56) (25) The numbers in parentheses express the compound number in Table II. 3-oxo-a-ionol, at least one enzymatic reaction is probable. Thus, the elucidation of the stereochemistry of the side chain in 3-hydroxy-,'1-ionol and 3-hydroxy-7,8-dehydro-,'1-ionol seem to be of great interest from the view point of the degradation mechanism of carotenoids.…”
Section: Lomentioning
confidence: 99%
“…12 ) 3-0xo-7,8-dihydroa-ionol (Blumenol C) has been reported to be present in the leaves of Rodocarpus blumei. 25 ) With respect to the configuration of the hydroxyl group, 3-hydroxy-{i-ionone has the same configuration as zeaxanthin. 26 ) This supports the assumption that 3-hydroxy-pionone is formed by the oxidative degradation of carotenoids such as zeaxanthin which has 3-hydroxyl group.…”
Section: Degradation Products Of Carotenoidsmentioning
confidence: 99%
“…The aglycone of blumenin, blumenol C, was first isolated from leaves of Podocarpus blumei. 43) Blumenin and a number of related cyclohexenone derivatives have been found in the AM roots of most gramineous plants, O. umbellatum, and solanaceous tobacco and tomato, and also the model legumes L. japonicus and Medicago truncatula. [44][45][46][47] These compounds differ in ring substitutions and in the nature and degree of glycosylation, including sugar moieties modified with a malonyl group.…”
Section: Am-specific Accumulation Of Mycorradicin and Cyclohexenomentioning
confidence: 99%